241 Atlas and dashboard of child and youth injury prevention. (1st September 2016) - Pike, Ian; Al-Hajj, Samar; Piedt, Shannon; Macpherson, Alison; ,
Abstract : Background: Visual Analytics (VA) is defined as 'the science of analytical reasoning facilitated by interactive visual interfaces'. An interactive VA system helps users make sense of complex and massive data and supports decision-making. The goal of this project was to develop an interactive web-based child and youth injury Atlas and Dashboard and populate it with existing and novel research data from the CIHR Team in Child and Youth Injury Prevention. The aim was to assist injury professionals, practitioners and policy makers to make informed and timely decisions and take action to improve child and youth injury prevention in Canada. Methods/description of the problem: Broad input from the injury prevention community in Canada was sought to finalise the operational requirements for the Atlas and Dashboard. This took place at several time points: 1) the early stages of development to inform the initial mock-up of the site, 2) once the data visualisations were created to determine if they were useful to users, 3) near completion of the site to obtain feedback on usability from the target audience. Visual Interaction Methodology, which helps users derive insights, acquire knowledge and optimise site use, was used to help stakeholders explore and analyse complex data. Results: Provincial level child and youth injury mortality, hospitalisation, drowning and transport data were made available to users in two different formats: 1) interactive data visualisations of injury trends and patterns, 2) user defined outputs from selectable menus allowing users to sort, view and query injury data. Injury professionals, practitioners and policy makers informed the look, feel and function of the site and provided feedback that improved the user experience. Conclusions: The Atlas and Dashboard integrates an interactive VA system into a website for child and youth injury prevention aimed at injury professionals, practitioners and policy makers in Canada.